2010
DOI: 10.1007/s13197-010-0061-x
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of pomace from apple processing industries: a review

Abstract: In large scale apple juice industry, about 75% of apple is utilized for juice and the remaining 25% is the by-product, apple pomace. In India, total production of apple pomace is about 1 million tons per annum and only approximately 10,000 tons of apple pomace is being utilized. Generally, apple pomace is thrown away, which causes environmental pollution. As the pomace is a part of fruit, it has potential for being converted into edible products. Apple pomace is a rich source of carbohydrate, pectin, crude fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
133
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(136 citation statements)
references
References 21 publications
0
133
0
3
Order By: Relevance
“…The waste generally refers to a heterogeneous mixture of peels, pomace and seed, with high content of water and insoluble carbohydrates, such as hemicellulose, 9% cellulose and 5% lignin. This waste is largely available, especially during harvesting season In large scale apple juice industry a large amount of wastes is produced, indeed about 75% of apple is utilized for juice and the remaining 25% is the by-product, apple pomace (Shalini and Gupta, 2010). Apple pomace is constituted by simple sugars (glucose, fructose, and sucrose) and is a rich source of carbohydrate, pectin, crude fiber, proteins, vitamins and minerals, and as such is a good source of nutrients, worth to be recovered.…”
Section: Vegetable and Fruitsmentioning
confidence: 99%
See 2 more Smart Citations
“…The waste generally refers to a heterogeneous mixture of peels, pomace and seed, with high content of water and insoluble carbohydrates, such as hemicellulose, 9% cellulose and 5% lignin. This waste is largely available, especially during harvesting season In large scale apple juice industry a large amount of wastes is produced, indeed about 75% of apple is utilized for juice and the remaining 25% is the by-product, apple pomace (Shalini and Gupta, 2010). Apple pomace is constituted by simple sugars (glucose, fructose, and sucrose) and is a rich source of carbohydrate, pectin, crude fiber, proteins, vitamins and minerals, and as such is a good source of nutrients, worth to be recovered.…”
Section: Vegetable and Fruitsmentioning
confidence: 99%
“…Furthermore, several microorganisms can use apple residues as a substrate for growth (Kosseva, 2011). Shalini and Gupta (2010) analyzed different uses of this byproduct: i) fuel purposes; ii) food products; iii) pectin extraction; iv) cattle feed; v) biotransformation; vi) source of fibers; vii) miscellaneous use. Due to large quantity of produced apple pomace, the preparation of single product would not be economically feasible and production of alternative products should be explored.…”
Section: Vegetable and Fruitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a pulsed electric field (PEF) with a belt-press system, Turka et al (2012) increased juice yield by 4.1% whilst Jaeger et al, (2012) reported increased efficiency using PEF of up to 11%. Despite such improvements to belt-press systems, a recent review by Shalini & Gupta (2010) still suggests that juicing produces around 25% waste. Of this waste, 20% is retrieved as animal feed and the rest (80%) is used for composting, landfill or incinerated (Dhillon et al, 2012).…”
Section: B25 Management Of Food Processing Residuementioning
confidence: 99%
“…A extração de pectina é considerada um processo de baixo custo operacional, resultando em moléculas usadas como aditivos alimentares (espessante ou estabilizante), com significativo valor no mercado, a exemplos da fabricação de geleias e de nutracêuticos, onde seu consumo pode reduzir os níveis de colesterol total e LDL, além de modelar a resposta glicêmica (BAKER, 1994;FENNEMA, 1996;SHALINI & GUPTA, 2010). As propriedades físico-químicas da pectina dependem das condições da matéria-prima selecionada para o seu isolamento e purificação (CHAN & CHAO, 2013), tendo como fases para sua obtenção: 1) extração do material, em meio aquoso à quente, ácido ou básico, com agentes quelantes ou por ação de enzimas (SOLER, 1995;PINHEIRO, 2007); 2) purificação do extrato líquido e 3) separação do extrato da pectina.…”
Section: Introductionunclassified